Opportunities and Strategies For Women's Economic Empowerment Through Online Media - Nita Ainun Nadjah; Abdul Mukhlis; Nurhannah Widiyanti; Sacandra Aji Rivaldi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The global Covid-19 pandemic has affected almost all lines of human life without exception, be iteconomic, educational, social, or other aspects. One of the sectors which, according to the author, isthe most affected is the economy. The implementation of social restrictions during Covid-19 hasreduced the income of some people and lose their jobs. Men and women alike are the objects that areharmed. However, there is an interesting phenomenon that deserves attention, namely, theproliferation of digital businesses carried out by women. The author tries to capture this phenomenonusing a qualitative descriptive method. Furthermore, the empowerment carried out by the author andthe team utilizes the SL (Service Learning) method. In addition, the author also tries to offer aconceptual formula in the form of a women's empowerment strategy based on simple observations inthe field. The result of this study of women's economic empowerment is the increase in women'screativity in making products that sell value through online marketing. It is hoped that thisempowerment activity will be able to elevate the dignity and independence of the community, especiallywomen.